(untitled) (Revista científica Olimpia, 2021)
The work addresses the insufficiencies that exist in first-year students in "Physical Culture" Cienfuegos, on cultural identity and the lack of activities to strengthen it. The Physical Education teacher, faithful to the ethical principles of sport, assumes the arduous task and responsibility of forming well-rounded students, capable of acting with dignity, proud of their history. (National and local), of cultural heritage, with a sense of belonging and identity, contributing to the strengthening of cultural knowledge through various recreational activities.